Factores asociados al esquema de vacunación incompleta en niños escolares de 5 – 12 años que acuden al centro de salud El Mamey, periodo mayo - agosto del 2024. - Basantes Quinatoa, Kevin Alexander (2024)
Universal access with high vaccination coverage and the sensitivity of the epidemiological surveillance system are fundamental strategies to achieve and sustain global public health goals, in the present research work related to the factors associated with the incomplete vaccination schedule in school children aged 5 - 12 years, aims to determine how the factors associated with the incomplete vaccination schedule influence school children aged 5 – 12 years who attend the El Mamey health center, period May - August 2024, for which a methodology with design is applied. mixed descriptive and explanatory approach, documentary and field modality, with inductive-deductive method to a specific population in all health professionals who are in number of 8 and all children with respiratory infection problems due to syncytial virus in a total of 233, the sample being 145 patients and 3 health professionals, to whom interviews and surveys were applied using the observation sheet and the questionnaire with open or closed questions as the information collection instrument, depending on the case, concluding that associated factors such as: poverty, little education of parents or caregivers, lack of knowledge of vaccines, fear, in addition to the location, access to health centers, beliefs and even institutional problems directly influence the incomplete vaccination schedule in school children aged 5 to 12 years who attend the El Mamey health center during the period from May to August 2024.